Evaluation of a large spectrum of patients who underwent thyroid surgery: an analysis of 462 cases - Ulusoy, Seçkin; Daşgın, Emel; Babaoğlu, Ahmet; Bıkmaz, Feridun; Sunal, Hakan; Selvioğlu, Recep; Baki Yılmaz, Hüseyin (ENT Updates, 2013)
Objective: To review and evaluate clinically and histopathologically a wide spectrum of thyroid surgery cases in our hospital, and to make a comparison between the results obtained and the complications encountered to the available data in the pertinent literature. Methods: A total of 462 patients who underwent thyroidectomy between January 2006 and June 2012 were evaluated retrospectively depending on their age, gender, scope of surgical operations, duration of surgery, complications involved, and the histopathological results. Results: The number of near-total thyroidectomy surgeries performed was161 (34.84%), Dunhill procedure was 156 (33.76%), subtotal thyroidectomy was 91 (19.69%), and total thyroidectomy was 54 (11.68%). In the histopathological evaluation, 435 of them were (94.1%) benign and 27 (5.8%) of them were of malignant thyroid mass. The number of benign thyroid pathologies was reported as 25 (5:41%) for Hashimoto's thyroiditis, 40 (8.65%) for chronic lymphocytic thyroiditis, 2 (0.43%) for granulomatous thyroiditis, 33 (7.14%) for follicular adenoma, and 335 (72.5%) for nodular regenerative hyperplasia. Twenty-seven patients (6.2%) were diagnosed as malignant and 26 of them were papillary carcinoma and1 of them was follicular carcinoma. Follow-up thyroidectomy was performed in 8 cases of malignancies and3 of them underwent neck dissection. Complications were seen in 39 (8.44%) patients in the postoperative period. Unilateral permanent vocal cord paralysis was detected in 14(3.03%) and bilateral permanent vocal cord paralysis were detected in 2 (0.43%) patients. Conclusion: Differentiation of thyroid masses as benign or malignant through ultrasound-guided fine needle aspiration biopsy should be performed more often to avoid unnecessary thyroidectomies. If any suspicious thyroid mass suggesting malignancy is present, near-total thyroidectomy or total thyroidectomy has to be performed firstly.